Instrumental Motivation of English Online Learning During Pandemic Covid-19 - I Gusti Ayu Vina Widiadnya Putri; Ida Bagus Gde Nova Winarta (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
This study aims to identify and analysed the Instrumental Motivation of Englishonline learning during pandemic covid-19. Teachers and learners must be consistent incarrying out learning in special conditions nowadays. A teacher has very important rolein fostering student motivation to take part in online learning, so the failures in theprocess of transferring knowledge to students can be minimized. This research isquantitative and descriptive qualitative study to examine Instrumental motivation inonline learning during pandemic covid-19. The random sampling was used in this study.The questionnaire was used as an instrument in this study. The questionnaire consists of12 questions as a test of instrumental motivation which is divided into three differenttypes of questions such as: academic motivation, individual motivation and socialmotivation. The responses obtained from the participants were classified into fivecategories according to Gardner's Attitude and Motivation (Jefiza, 2017), such as; stronglyagree, agree, doubt, disagree and strongly disagree. It was found that the motivation ofstudents in online learning conducted in class was to finish on time. The total mean ofacademic aspect is 3.61 at the moderate level. Meanwhile, for the personal aspect, it wasfound that the value for the total mean of the personal aspect was 3.69 at a high level, andthe mean of social aspects on instrumental motivation was 3.89 at a high level. It can beshown that, the students still have high motivation in taking online learning even duringthe pandemic covid-19.